2004
DOI: 10.1038/sj.onc.1208199
|View full text |Cite
|
Sign up to set email alerts
|

Lyn deficiency reduces GATA-1, EKLF and STAT5, and induces extramedullary stress erythropoiesis

Abstract: In vitro studies have implicated the Lyn tyrosine kinase in erythropoietin signaling. In this study, we show that J2E erythroid cells lacking Lyn have impaired signaling and reduced levels of transcription factors STAT5a, EKLF and GATA-1. Since mice lacking STAT5, EKLF or GATA-1 have red cell abnormalities, this study also examined the erythroid compartment of Lyn À/À mice. Significantly, STAT5, EKLF and GATA-1 levels were appreciably lower in Lyn À/À erythroblasts, and the phenotype of Lyn À/À animals was rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 72 publications
(94 reference statements)
7
65
0
1
Order By: Relevance
“…Importantly, the absence of Lyn, or prolonged activation of Lyn, have deleterious consequences for the hemopoietic compartment in vivo (26,27,55). The data presented here add to the understanding of the intricate mechanisms involved in the control of Src family kinases.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Importantly, the absence of Lyn, or prolonged activation of Lyn, have deleterious consequences for the hemopoietic compartment in vivo (26,27,55). The data presented here add to the understanding of the intricate mechanisms involved in the control of Src family kinases.…”
Section: Discussionmentioning
confidence: 88%
“…Cells were stimulated with Epo (5 units/ml) in media containing T 3 depleted FCS (36), and hemoglobin production detected by benzidine staining (21). Splenic erythroblasts were isolated from phenylhydrazinetreated Lyn ϩ/ϩ and Lyn Ϫ/Ϫ mice as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] JAK2 is recognized as the kinase involved in initiation of Epo receptor signaling, 1 whereas Lyn, a member of the Src family of tyrosine kinases (SFKs), has been implicated as a key secondary kinase. [5][6][7][8][9][10] In vitro studies established a role for Lyn in Epo receptor signaling 6,11 and demonstrated that Epo signaling in immortalized J2E-derived cells appeared identical to primary erythroid cells. 6,9,11 Subsequent studies using Lyn 2/2 mice consolidated the importance of this SFK for early erythroid cell expansion and late-stage maturation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In vitro studies established a role for Lyn in Epo receptor signaling 6,11 and demonstrated that Epo signaling in immortalized J2E-derived cells appeared identical to primary erythroid cells. 6,9,11 Subsequent studies using Lyn 2/2 mice consolidated the importance of this SFK for early erythroid cell expansion and late-stage maturation. [8][9][10] Removal, or inhibition, of Lyn attenuates the ability of erythroid cells to differentiate in response to Epo.…”
Section: Introductionmentioning
confidence: 99%